To evaluate first aid knowledge on burns management amongst high risk groups. Issue 1 (July 2017) - Lam, Nguyen Nhu; Li, Frank; Tuan, Chu Anh; Huong, Ho Thi Xuan
Abstract: This survey aims to evaluate first aid knowledge for the management of burns cases amongst high risk groups. Methods: A survey was conducted on 674 workers including fire fighters, and workers in electrical power and oil industries. The contents of the survey focused on demographic criteria, first aid measure for burn accidents and source of information. Results: 29.5% of participants achieved the desirable score over 75%. The incidence of participants who reported knowing to use cool fresh water to reduce the temperature of the burn wound was 86.1%. In addition, a higher knowledge level was significantly seen in a sub-group of younger, male workers, as well as those who took part in training courses ( p  < 0.001). Different knowledge levels were also recorded between sub-groups of workers ( p  < 0.01). The information source mostly came from multimedia, and only 8% via formal school education. Conclusion: First aid knowledge of high risk workers was significant limited including theoretical and practical scenerio for burns accidents. It will be necessary to plan and conduct further training courses for these groups.